The influence of crack tip shielding on fatigue crack propagation (Fracture and Structural Integrity, 2017)
The fatigue crack propagation is one of the major problems and of the real concern in the evaluation of the structural integrity of components. This is due to the fact that once a fatigue crack has been detected it is also known its effect on the component; respectively it will cause failure at one time. In this situation, the problem is focused on determining the character of propagation of the crack so that it can be estimated and respectively delayed as possible the failure moment. The fatigue crack propagation character is determined by the stress state at the crack tip and the behavior of the material in which the crack is propagates. One of the phenomena with great influence on the fatigue crack propagation character is the crack tip stress shielding phenomena. In this paper the overloading effect is explained in terms of crack tip shielding mechanisms that guide the fatigue crack growth in plastic zone. The results indicate a change of fatigue crack propagation character once its tip enters into a plastic zone.
Keywords: Fatigue crack growth rate; Crack tip shielding; Crack closure; Overloading cycle; Plastic zone